Biodiversity Assessment of Foxtail Millet (Setaria italica L.) Genotypes Based on RAPD Marker - ARDIE, Sintho Wahyuning; Khumaida, Nurul; Fauziah, Nurul; Yudiansyah, Yudiansyah (Journal of Tropical Crop Science, 2017)
Foxtail millet (Setaria italica L.) is an important crop in areas where harsh environmental conditions limit crop productivity, including in high salinity and drought prone areas. In Indonesia millet is cultivated in certain areas; however, superior varieties are less developed in the country. The objective of this study was to analyze the genetic diversity among foxtail genotypes using RAPD markers. Genomic DNA of ten foxtail millet genotypes was amplified using 26 random primers through RAPD analysis. Of these primers, 22 produced reproducible amplicons and were polymorphic among the 10 foxtail millet genotypes. The number of polymorphic markers for each primer varied from 1 (primer E15) to 14 (primer M17). The amplified product size ranged from 120 to 2500 base pairs (bp). A dendrogram constructed based on the UPGMA clustering method put all genotypes in 5 distinct groups at 0.64 coefficient level. Diverse genotypes identified in this study can be used as potential parents in an efficient crop improvement program.